XRF core scanning yields reliable semiquantitative data on the elemental composition of highly organic-rich sediments: evidence from the Füramoos peat bog (Southern Germany) - Kern, Oliver A.; Koutsodendris, Andreas; Mächtle, Bertil; Schukraft, Gerd; Scholz, Christian; Pross, Jörg (The science of the total environment, 2019)
X-ray fluorescence core scanning (XRF-CS) has become a standard tool in paleoenvironmental studies. Allowing rapid, inexpensive and non-destructive analysis of the elemental composition of sediment cores at high spatial resolution, it is ideally suited for the reconstruction of short-term climatic change. However, its applicability to cores consisting of peat and other highly organic-rich sediments has yet remained poorly explored. We have therefore investigated the application of XRF-CS to two cores consisting of ombrotrophic peat and of fen peat and organic-rich muds of Late Glacial-Holocene and Eemian age, respectively, from a peat bog in Southern Germany using an Avaatech 4th-generation XRF core scanner. The XRF-CS-derived distributions of elements widely used in (paleo)environmental research (i.e., Al, Ca, Fe, K, Mg, Mn, S, Si, and Ti) were systematically compared to the results of inductively coupled plasma optical emission spectrometry analyses. For the Late Glacial-Holocene peat core, XRF-CS yielded reliable semiquantitative data for the majority of the investigated elements (i.e., Ca, Fe, K, Mn, S, Si, and Ti), with R2≥0.5. XRF-CS of the Eemian fen peat and organic-rich muds yielded reliable data for Al, K, S, and Ti (R2≥0.5) and, to a lesser extent, for Fe (R2=0.46). and Si (R2=0.25). This indicates that XRF-CS allows to semiquantitatively reconstruct the distribution of the majority of paleoclimatically relevant elements in peat and other highly organic-rich sediments. Hence, XRF-CS is well suited to complement the analytical toolbox for the paleoenvironmental study of such sediments.
Gesehen am 09.09.2019